Profissional da informação: o bibliotecário e seu perfil frente às tecnologias de informação e comunicação - REIS, Raquel de Souza (2017)
Study of the technological challenges that the librarian faces in order to practice the profession, expanding its field of action in front of its object: information. For this, the general objective was to analyze the impact of Information and Communication Technologies (ICTs) on the professional profile of the Librarian, observing the skills and competences required by the labor market. To this end, the specific objectives were: to identify the skills and competences of the librarian; Described the improvements that the TICs provide to the libraries with regard to the services provided to the user; The informational competence of the Librarian with the use of the TICs was analyzed. The methodology used for the construction of the work was carried out through bibliographical research with a qualitative approach. As a result, it was emphasized that the impact of ICTs on the profile of the librarian, provided new fields of action and informational competence, focused on the skills of handling technological programs, which began to compose the products and services of informational institutions. It concludes with the analysis that ICTs should be appropriate and used by librarians, as an important tool in the services and updating of the professional.